Esophageal injuries - Dąbrowski, Andrzej; Solecki, Michał; Mach-Lichota, Elżbieta; Skrzypek, Agata; Maciejewski, Ryszard; Szukała, Magdalena (Polish Journal of Public Health, 2010)
For the surgical treatment of esophageal injuries is extremely important, that you read the anatomy of this organ. Esophagus as a musculo – membranous tube is another section of the gastrointestinal tract, the vestibule of the oral cavity, mouth and throat, which in its longitudinal course connects the throat to the stomach. In the literature exchanged a number of reasons that can cause damage, including perforation of the esophagus. The summary table shows that the largest were: iatrogenic injures, which accounted for 43% of all lesions of the esopha-gus, other injures were respectively: spontaneous rupture of 16%, 19% - external causes of injury, damage caused by foreign bodies 7%, perforation associated cancers – 4% and other 3%. In the case of injury of the esophagus (regardless of the esophagus factors) should be ruled out perforation of this organ. This follows from the fact that the perforation of the esophagus leads to purulent mediastinitis, pleural inflammation, sepsis and death. Comeback function of this organ is strategic purpose of treatment of damage of gullet. Factor , no doubt which plays important role in success of treatment with perforation of gullet time of taking of treatment ill. At least there is period of shutdown of perforation of gullet finish according to numerous authors after 24 hours in half of case accidentally in place of primary damage of wall of organ every reparation procedures secondary leakage 12 hours. Strict association exists among early diagnosis, operative treatment but with damage of wall of gullet mortality ill. Early diagnosis of perforation allows in connection with operative treatment survival 93% however late diagnosis boots mortality for 30% (> 24 h).